Layered Peptide Array for Multiplex Immunohistochemistry - Gannot, Gallya (American Society for Investigative Pathology, 2007)
Layered peptide array is a new methodology for multiplex molecular measurements from two-dimensional life science platforms. The technology can be used in several different configurations depending on the needs of the investigator. Described here is an indirect layered peptide array (iLPA) that is capable of measuring proteins on a solid surface, such as target antigens on a tissue section. A prototype iLPA system was developed and subsequently examined for reproducibility and specificity and then compared with standard immunohistochemistry. Semiquantitative, multiplex proteomic analysis of histological sections was achieved with up to 20 membranes. The experimental variability was 18%. Overall, the data suggest that iLPA technology will be a relatively simple and inexpensive method for molecular measurements from tissue sections.